Optimized Microwave Reflux Extraction and Antioxidant Activities of Piperine from Black and White Piper Nigrum - Olalere, Olusegun Abayomi; Nour, A. H.; Alara, Oluwaseun Ruth; Habeeb, Omar Abed (Bangladesh University of Engineering and Technology, 2017)
In this study, the microwave reflux technique was employed to extract piperine from black and white pepper. This is due to its ability to combine the microwave and the conventional solvent extraction together with a high degree of selectivity and quality extract. The extraction process was optimized using theL9-Taguchi experimental design. This investigated the effects of four independent factors (irradiation time (x1), microwave power level (x2), feed particle size (x3) and molar ratio (x4)) on piperine yield. Antioxidant activity of the oleoresin extracts were later evaluated using DPPH (1, 1-diphenyl-1-picrylhydrazyl) radical scavenging assay. The optimum extraction condition in black pepper refluxation was attained at 90 min irradiation time (x1), 350 W power level (x2), 0.105 mm feed particle size (x3) and 10 mL/g molar ratio (x4) with an extremum ranking in decreasing order of x3> x4> x2> x1.However,from the white pepper refluxation an optimum condition was achieved at 120 min irradiation time (x1), 350 W power level (x2), 0.300 mm feed particle size (x3) and 6 mL/g molar ratio (x4) with a corresponding decreasing extremum order of x1> x4> x2> x3.From the results obtained from concentration-dependent radicals scavenging activity it was concluded that white oleoresins extract were much higher in inhibitory activity than that of black oleoresin extract.